An alternative test of tackling ability in rugby league players - Speranza, M. J. A.; Gabbett, T. J.; Greene, D. A.; Johnston, R. D.; Townshend, A. D.; O`Farrell, B, (International Journal of Sports Physiology and Performance, 2018)
This study investigated the relationship between 2 tests of tackling ability, muscle strength, and power in semiprofessional rugby league players. Thirty-one players, 19 first-grade and 12 second-grade, underwent tests of muscle strength (1-repetition-maximum bench press, chin-up, and squat) and power (plyometric push-up and countermovement jump). Tackling ability was assessed via video analysis of under-and over-the-ball tackle drills. The first-grade players had significantly greater scores in both the under-the-ball (P=.03, effect size [ES]=0.84, 95% CI 0.07-1.50) and over-the-ball tackling-ability tests (P<.001, ES=1.86, 95% CI 0.83-2.52) than the second-grade players. A large, significant relationship was found between under- and over-the-ball tackling ability (r=.55, 95% CI .24-.76, P=.001). Lower-body strength (r= 37, 95% CI .02-.64, P=.04) was moderately associated with under-the-ball tackling ability, whereas over-the-ball tackling ability was moderately associated with plyometric push-up performance (r=.39, 95% CI .04-.65, P=.03). This study found that over-the-ball tackling ability was significantly associated with under-the-ball tackling in semiprofessional rugby league players. Furthermore, it was found that, compared with the second-grade players, the first-grade players had superior tackle ability in both tackle drills. In this study it was observed that plyometric push-up peak power was significantly related to over-the-ball tackling ability and absolute lower-body strength was associated with under-the-ball tackling ability. These findings provide skill coaches and strength and conditioning staff a greater understanding of elements that contribute to effective tackling ability.